The Role of Supply Chain Integration in Sustainable Performance of Thai Manufacturing Organizations: A Mediation effect of Supply Chain Performance - Witthaya Mekhum (International Journal of Supply Chain Management, 2020)
Sustainable performance is a serious concern for manufacturing organizations and a challenge for supply chain in the 21st century. Particularly a challenge is how to stimulate firms’ social and environmental attentiveness and put integrated activates into practice for sustainable performances. This study examine the role of supply chain integration in sustainable performance of Thai manufacturing firm with mediating role of supply chain performance. For the fulfillment of the objective of this research, the data was collected from the plant managers and supply chain managers via questioners. It is found that internal integration and logistic integration positively influence the sustainable performance of manufacturing organizations. Supply chain integration could enhance the supply chain performance of the firm that ultimately increases the sustainable performance of the organizations. The study offers a new empirical evidence for managerial decision and it can contribute valued perceptions for manufacturing firms in the strategy development regarding supply chain. However, this study used only internal integration and logistic integration, the other important element of supply chain such as customer integration and supplier integration, could be used by researchers for future research.